Navigating The Circular Economy in Sustainable Ecotourism: A Case of Margo Utomo Eco Resort - Wibisono, Akbar; Novani, Santi (Journal Integration of Management Studies, 2025)
As environmental pressures intensify, the tourism industry faces increasing demand to transition from linear, waste-intensive practices to sustainable models. This case study investigates how Margo Utomo Eco Resort, an established agro-tourism site in East Java, Indonesia, can operationalize circular economy (CE) principles. Although the resort currently employs eco-conscious practices such as composting, local sourcing, and biogas generation, these efforts remain fragmented and informal. A qualitative approach was adopted, including internal document review, staff interviews, site observations, and a focus group. Strategic analysis was conducted using SWOT and PESTLE frameworks to identify key barriers and opportunities. Circular business model archetypes were applied to develop intervention options, which were then prioritized through Multi-Criteria Decision Analysis (MCDA). The SMARTER method (Simple Multi-Attribute Rating Technique Exploiting Ranks) was used to rank strategies based on environmental impact, cost, feasibility, and guest alignment. The top-ranked strategies were: (1) upgrading the composting system, (2) adopting refillable and biodegradable toiletries, and (3) implementing a preventive maintenance plan using in-house resources. These were selected for their high impact and feasibility within existing operational constraints. The findings demonstrate that sustainability transitions in small-scale tourism enterprises need not rely on advanced technologies. Incremental improvements, grounded in local capacity and structured prioritization, can yield significant progress. This study offers a replicable roadmap for integrating circularity in similar hospitality contexts.